2009
DOI: 10.1159/000197104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early Parkinson’s Disease

Abstract: The management of early Parkinson’s disease (PD) involves the treatment of motor symptoms, and, increasingly, non-motor symptoms. Given the fast pace of clinical research in PD, clinicians are faced with the challenge of integrating the latest findings into the ongoing care of individual PD patients. Part 1 of this 2-part article reviews efficacy and safety data for the newest PD treatment options, as well as for established therapies. Part 2 of the article, presented here, reviews key data relevant to the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 145 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that the use of dopamine agonists has not been shown to correlate to olfaction. 16 We confirmed this result in our subset. In this study, the DBS group did have a higher average use of dopamine agonists, however most of this difference was due to a single outlier with very significant dosing.…”
Section: 2supporting
confidence: 83%
“…Previous studies have shown that the use of dopamine agonists has not been shown to correlate to olfaction. 16 We confirmed this result in our subset. In this study, the DBS group did have a higher average use of dopamine agonists, however most of this difference was due to a single outlier with very significant dosing.…”
Section: 2supporting
confidence: 83%
“…This suggests that deficient cholinergic modulation of circuit function can be evident early, before motor symptoms, which could contribute to early cognitive dysfunction. On the other hand, while acetylcholinesterase inhibitors, including donepezil, have been used clinically to ameliorate cognitive decline in demented PD and Alzheimer’s patients (Simuni et al, 2009; Sharma, 2019; Armstrong and Okun, 2020), their effectiveness for improving mild cognitive impairment in early-stage PD is equivocal (Mamikonyan et al, 2015; Baik et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, DA replacement therapy using levodopa remains the gold standard for symptomatic relief in PD patients. However, due to the well-documented limitations of long-term DA replacement therapy and its widespread debilitating side-effects, neuroprotective strategies that slow or halt the disease progression are urgently needed ( Simuni et al, 2009a ; Simuni et al, 2009b ; Sarkar et al, 2016 ; Fabbri et al, 2020 ). Mitochondrial dysfunction, oxidative stress, neuroinflammation and impaired protein degradation are implicated as potential pathological mechanisms of PD, but key downstream signaling targets contributing to nigral dopaminergic neuronal degeneration are not well established.…”
Section: Introductionmentioning
confidence: 99%